Dear Sam.....Sumasaiyo, Juan - Cabangan, Jun.; Lamangan, Joel J. Lamangan; Matilac, Rosalie; Santiago, Emy Santiago; Ateneo Center for Social Policy and Public Affairs; Foundation for Media Alternatives ([Quezon City] The Center, 1990)
A documentary on the RP-US relations.
Music, Gary Granada, Patatag, Pol Galang, Bonjie Pascua.
Keywords: United States -- Foreign relations -- Philippines; Philippines -- Foreign relations -- United States; Sociology